Numerical and Experimental Study on Reasonable Coverage of Shot Peening on ZGMn13 High Manganese Steel - Yuan, Haiyang; You, Zhangping; Zhuo, Yaobin; Ye, Xiaoping; Zhu, Liangliang; Yang, Weibo (Frontiers in Materials, 2022)
Shot peening technology is usually employed to improve the ability of mechanical parts to resist failure due to fatigue and wear. It is often used to strengthen the surface of a target, but the induced residual stress and its distribution with respect to the coverage can affect the performance of the shot peening process. In this study, a comprehensive numerical and experimental study was conducted to overcome these issues. Using numerical simulation we found that both the surface and subsurface residual stress increases with the increase of the coverage before stabilizing. Quantitative analysis using the Entropy Method indicates that under the shot peening parameters considered in the simulation coverage of 200% is best for the shot peening of ZGMn13 High Manganese Steel. The following experimental study agreed with the corresponding numerical data for the residual stresses at varied depths from surface to subsurface with errors of less than 25%. Thus, the related research outcomes can guide the shot peening process to obtain the optimized surface strengthening of the target.